The Influence of Green Human Resources Management on Thriving at Work and Green Commitment Through Green Self-Efficacy as a Mediating Variable in Hospitals Batam - Hakim, Muhammad Adib Taufiqul; Muchsinati, Evi Silvana; Asri, Dhita Hafisha (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to identify and analyze the influence of Green Human Resource Management (GHRM) on thriving at work and green commitment, with green self-efficacy as a mediating variable in hospitals in Batam. The study population includes all hospital staff/employees working and registered in the city of Batam, with a sample size of 200 respondents. Data analysis utilized Structural Equation Modeling – Partial Least Squares (SEM-PLS) with the assistance of the SmartPLS 3 application. The research findings all six hypotheses were supported. The novelty of this study lies in the finding that Green Self-Efficacy serves as a significant mediating variable.